Job Search Strategies for Older Job Hunters: Addressing Employers’ Perceptions - Gibson, Kevin J.; Zerbe, Wilfred J.; Franken, R. E. (Canadian Journal of Counselling and Psychotherapy, 1992)
This study analyzed responses from 651 employers to the question: "What is the major reason why the mature unemployed so often have difficulty finding work?" Five major barriers that limit the re-employrnent opportunities of older job hunters were identified from employers' responses: 1) the older job hunter is perceived as being unqualified to perform the duties associated with contemporary employment; 2) the older job hunter is perceived as being more expensive to employ; 3) the older job hunter is perceived as being difficult to integrate into the corporate culture; 4) the older job hunter is perceived as being the victim of discrimination; and 5) the older job hunter is perceived as lacking appropriate job-search skills. Each of the barriers to re-employment is described in terms of the accuracy of the claim, and possible mechanisms for overcoming each barrier are discussed. It is concluded that regardless of the accuracy of employers' perceptions it is ultimately the responsibility of the older job hunter to address employers' concerns.